Influence of pyroligneous acid on cucumber cultivation under organoponic conditions - Rondón-Estrada, Liliana; Gómez-Padilla, Ernesto; Guevara-Hernández, Francisco; La O-Arias, Manuel; Reyes-Sosa, Mariela; Viltres-Rodríguez, Roberto (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Pyroligneous acid is recognised as an effective biostimulant in a wide range of crops, improving processes such as germination, growth and yield, as well as inducing stress tolerance and increasing plant resistance to adverse conditions. To evaluate the effect of applying pyroligneous acid (PA) foliarly and on the substrate on the growth, development and yield of cucumber crops, an experiment was set up under organoponic conditions in Bayamo, Granma, Cuba. Seven treatments were used, consisting of PA doses of 5 mL.L-1 foliar (FD1), 10 mL.L-1 foliar (FD2), 15 mL.L-1 foliar (FD3), 5 mL.L-1 substrate (SD1), 10 mL.L-1 (SD2), 15 mL (SD3) and an absolute control. The treatments were established using a completely randomised design. Each treatment was replicated three times, with a sample size of 15 plants per replicate. The product was applied at 7, 14 and 21 days after germination. At 21 days after germination, stem length (cm), stem base diameter (cm), number of leaves, leaf diameter and length (cm), number of branches formed per plant and yield (t.ha-1) were evaluated. The application of PA, both on the leaves and on the substrate, promoted plant growth and development at doses of 5 and 10 mL.L-1. Similarly, the yield-related variables also showed improvements with the application of the product, highlighting that the greatest stimulation was observed when the dose of 5 mL.L-1 was applied foliarly.